From light to heavy: addressing gaps in rare earth element extraction at the Lynas advanced materials plant - Zulkifli, Norazihan; Shoparwe, Noor Fazliani; Yusof, Abdul Hafidz; Abdullah, Ahmad Zuhairi; Ahmad, Mohammad Norazmi (UMK Press, 2024)
The Lynas Advanced Materials Plant (LAMP) in Kuantan, Malaysia, exemplifies sustainable practices in rare earth element (REE) separation processes through its efficient solvent extraction techniques using 2-ethylhexyl phosphonic acid mono2-ethylhexyl ester (HEH/EHP or P507) and di-2ethylhexyl-phosporic acid (D2EHPA or P204) to separate REEs from monazite ore sourced from Mt. Weld, Australia. LAMP achieves a remarkable 99% yield for light REE separation in areas such as lanthanum, cerium, praseodymium, and neodymium. It faces challenges separating heavy REEs due to the low content in its concentration to be cost-effective. This limitation underscores the need for improved solvents or alternative methods like ion exchange to enhance heavy REE recovery, particularly yttrium, gadolinium, terbium, and dysprosium, which is of interest to Malaysia to separate its non-radioactive heavy REE from ion-adsorbed clay. Insights from LAMP's processes offer valuable lessons in developing robust REE separation strategies that align with global demand, green technology, and environmental and social impact